2003
DOI: 10.1074/jbc.m212759200
|View full text |Cite
|
Sign up to set email alerts
|

An Ile-568 to Asn Polymorphism Prevents Normal Trafficking and Function of the Human P2X7 Receptor

Abstract: The P2X 7 receptor is a ligand-gated channel that is highly expressed on mononuclear cells and that mediates ATP-induced apoptosis of these cells. Wide variations in the function of the P2X 7 receptor have been observed, in part because of a loss-of-function polymorphism that changes Glu-496 to Ala without affecting the surface expression of the receptor on lymphocytes. In this study a second polymorphism (Ile-568 to Asn) has been found in heterozygous dosage in three of 85 normal subjects and in three of 45 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(175 citation statements)
references
References 42 publications
9
166
0
Order By: Relevance
“…Three loss-of function SNPs (T357S, E496A, and I568N) and one gain-of-function SNP (Q460R) are located in the long intracellular domain [54][55][56]58]. These loss-of-function polymorphisms lead not only to reduced P2X 7 pore function but also to impaired ATP-induced mycobacterial killing by macrophages [56,60,61,81,82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three loss-of function SNPs (T357S, E496A, and I568N) and one gain-of-function SNP (Q460R) are located in the long intracellular domain [54][55][56]58]. These loss-of-function polymorphisms lead not only to reduced P2X 7 pore function but also to impaired ATP-induced mycobacterial killing by macrophages [56,60,61,81,82].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these have not been validated at the population genetic level and their functional effects are unclear. Five loss-of-function nonsynonymous allelic SNPs in P2X 7 have been described to date, of which three are located in the carboxy-terminal cytoplasmic tail (T357S, E496A, and I568N) and two are in the extracellular loop [54][55][56][57][58]. Cabrini et al have characterized the first gain-of-function polymorphism identified (H155Y) [59].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms that have been identified within the coding region of the human P2X7 receptor have a wide range of outcomes, such as gain-of-function [81], loss-of-function [82,83], impairment of cytokine release [84,85], and altered cell death [86]. The relatively common Glu496Ala polymorphism results in reduced pore-forming ability [82] without altering channel function [87], whereas the Ile568Asn polymorphism prevents normal channel trafficking and function [88]. In this regard, Ohlendorff et al found that Glu496Ala and Ile568Asn single-nucleotide polymorphisms in the human P2X7 receptor are associated with 10-year fracture risk in postmenopausal women [79].…”
Section: Physiological Function Of P2x7 Receptors In Osteoclastsmentioning
confidence: 99%
“…In addition, one polymorphism was proven to impair ATP-induced IL-1β release from human monocytes and one to affect normal trafficking of this receptor Wiley et al, 2003). If the role of the P2X7 receptor in tooth movement is shown in an experimental model controlling for multiple variables, it could provide a strong base for association studies of these polymorphisms with ERR, and rate of tooth movement.…”
Section: P2x7 Receptor: a Possible Mediator Of Orthodontic Mechanotramentioning
confidence: 99%